Tailoring SOFC Electrode Microstructures for Improved Performance. Issue 23 (21st June 2018) - Connor, Paul A.; Yue, Xiangling; Savaniu, Cristian D.; Price, Robert; Triantafyllou, Georgios; Cassidy, Mark; Kerherve, Gwilherm; Payne, David J.; Maher, Robert C.; Cohen, Lesley F.; Tomov, Rumen I.; Glowacki, Bartek A.; et al.
Abstract: The key technical challenges that fuel cell developers need to address are performance, durability, and cost. All three need to be achieved in parallel; however, there are often competitive tensions, e.g., performance is achieved at the expense of durability. Stability and resistance to degradation under prolonged operation are key parameters. There is considerable interest in developing new cathodes that are better able to function at lower temperature to facilitate low cost manufacture. For anodes, the ability of the solid oxide fuel cell (SOFC) to better utilize commonly available fuels at high efficiency, avoid coking and sulfur poisoning or resistance to oxidation at high utilization are all key. Optimizing a new electrode material requires considerable process development. The use of solution techniques to impregnate an already optimized electrode skeleton, offers a fast and efficient way to evaluate new electrode materials. It can also offer low cost routes to manufacture novel structures and to fine tune already known structures. Here impregnation methodologies are discussed, spectral and surface characterization are considered, and the recent efforts to optimize both cathode and anode functionalities are reviewed. Finally recent exemplifications are reviewed and future challenges and opportunities for the impregnation approach in SOFCs are explored. Abstract : Surface modification of a solid oxide cell electrode via a solution impregnation method is a powerful way to improve electrochemical performance. Here the authors discuss various aspects of impregnation, review recent efforts in the field, and look at spectroscopic and surface characterization techniques.